Numerical analyses of energy balance and installation mechanisms of large-diameter tapered monopiles by impact driving. (15th December 2022) - Chen, Fuquan; Liu, Liyang; Lai, Fengwen; Gavin, Kenneth; Flynn, Kevin N.; Li, Yida
Abstract: Large-diameter monopiles are widely used as the foundation to support offshore wind turbines (OWTs) in shallow coastal waters. The benefits of small-to-medium diameter tapered piles have been reported in the past. The potential use of large-diameter tapered monopiles installed by impact driving to support OWTs is thus presented, and then comparatively assessed by numerical analyses in terms of energy balance and installation mechanisms. A three-dimensional large deformation finite element (3D-LDFE) model of monopiles driven in clay was developed using a Coupled Eulerian-Lagrangian (CEL) approach. An advanced user-defined hypoplasticity clay (HC) model was employed to model undrained kaolin clay, featuring nonlinear behavior from small strain to large strain. The force-time curve defined by the operating data of a state-of-the-art hammer in the offshore industry was inputted to explicitly model impact driving. Better agreement between the measured and the simulated results was observed to validate the accuracy of the numerical model. The numerical results obtained give greater confidence to the future use of large diameter tapered monopiles for OWTs. Highlights: The concept of large-diameter tapered monopiles is presented for offshore industry. An advanced user-defined hypoplasticity clay model is programmed to model seabed soils. Installation mechanisms and energy balance of various shapes of monopiles driven in clays are comparatively studied. The potential use of large diameter tapered monopiles for supporting OWTs is confirmed.